Keefektifan Layanan Bimbingan Kelompok Dengan Teknik Role Playing Untuk Mengurangi Perilaku Agresif Siswa - Kusumawati, Eny; Wahyunigsih, Diana Dewi; Setyonugroho, Imam (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
The provision of group guidance services with role playing technique aims to reduce aggressive behavior, because in this role playing technique students are given a description related to aggressive behavior that must be reduced so as not to become disruptive in megajar learning activities as well as the surrounding environment. The purpose of this study was to find out the effectiveness of group guidance services with role playing techniques to reduce aggressive behavior. This research is a pre-experimental research with the design of One Group Pretest-Posttest Design research, which is research using one group that acts as the subject of experimentation. Based on the results of the study, it is known that the frequency of aggressive behavior can be reduced through group guidance services with role playing techniques in elementary school students. This is evidenced from the results of data analysts using T-test where obtained a significant value of 0.000 <0.05 , it can be concluded that there is a significant difference between the results of pretest and postes values. These results show that Ho was rejected and Ha accepted. Thus it can be stated that group guidance services with role playing techniques affect the frequency of aggressive behavior.